Relationship of UK with the foreign markets after Brexit: Challenges and opportunities - Natalia Minut; Asim Majeed; Paul Bocij; Ayesha Asim; Mahmood Ali (International Journal of Management and Data Analytics)
The United Kingdom voted to leave the European Union in 2016, a challenging process that took place. Brexit was finalized on 31st January 2020, and after the transition period, the United Kingdom is not part of the European Union. The purpose of this research is to fill the gaps concerning how Brexit has and will affect the United Kingdom’s relationship with the European Union. The researcher conducts a study investigating the disruptive effects of Brexit and some of the organizational responses undertaken by companies in Britain. However, to conduct this study, the research focuses specifically on the Fortnum and Mason company as representing the retail industry. The chosen research method for this study is mixed-method research. This method will allow the researcher to acquire a broader picture of the topic under study. A pragmatic approach was used due to the study's nature as it is mainly grounded in the reality of many companies in the United Kingdom. This research paper will be valuable to retail firms and decision-makers who experience the uncertainties discussed in the study.